A novel method for determining the three dimensional variation of non-linear thermal resistance at the mold-strand interface in billet continuous casting process. (December 2020) - Jayakrishna, Pedduri; Chakraborty, Saurav; Ganguly, Suvankar; Talukdar, Prabal
Abstract: A three-dimensional numerical model has been developed to study the turbulent flow of the molten steel, heat transfer from the solidifying strand to the cooling water and the subsequent solidification within the mold of an industrial billet continuous casting process. Particular attention is paid to calculate the unknown non-linear thermal resistance at the mold-strand interface, based upon a physical formulation. The model results are validated with the data available in the literature, as well as from plant experimental data. Recirculation flows are observed near the mold walls, causing remelting of solidified shell. The results obtained from the simulations show that one of the major reasons for higher value of solidified shell thickness at the corner region than that at the off-corner region is the nature of recirculatory flows. The thermal resistance is found to vary along the casting direction as well as across the mold face. The plant data of solid shell thickness of the strand at mold exit shows that the current model involving physical formulation of thermal resistance at the mold-strand interface, provides a better estimation of the thermal behavior, compared to previous models involving empirical formulation for the thermal resistance or heat flux profiles at the interface.